2013
DOI: 10.1021/es403781z
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risk of Nonylphenol in China Surface Waters Based on Reproductive Fitness

Abstract: It has been recognized that ecological risk assessment based on traditional endpoints of toxicity are unable to provide adequate protection because some chemicals may affect reproductive fitness of aquatic organisms at much lower concentrations. In this paper, predicted no effect concentrations (PNECs) for 4-nonylphenol (NP) were derived based either on endpoints of survival, development, and growth or on some nonlethal biomarkers of reproduction, biochemical and molecular biology data. The PNECs derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(37 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…A much lower PNEC was derived by Crain et al , with a value of 0.03 µg/L based on chronic physiological endpoints. In addition, the calculated PNEC for 4‐NP with a value of 0.721 µg/L was comparable to that derived by the European Commission and Jin et al , with values of 0.33 and 0.12 µg/L, respectively. Overall, differences in the PNECs from different sources were likely attributable to different distribution methods (SSD and SSWD), different statistical extrapolation approaches (e.g., log‐normal and log‐triangular), toxicity data on the basis of different types of endpoints, test media (freshwater and seawater), and assessment factors (values range 1–5).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A much lower PNEC was derived by Crain et al , with a value of 0.03 µg/L based on chronic physiological endpoints. In addition, the calculated PNEC for 4‐NP with a value of 0.721 µg/L was comparable to that derived by the European Commission and Jin et al , with values of 0.33 and 0.12 µg/L, respectively. Overall, differences in the PNECs from different sources were likely attributable to different distribution methods (SSD and SSWD), different statistical extrapolation approaches (e.g., log‐normal and log‐triangular), toxicity data on the basis of different types of endpoints, test media (freshwater and seawater), and assessment factors (values range 1–5).…”
Section: Discussionsupporting
confidence: 85%
“…Levels of BPA in the water body of Tianjin City were comparable to those detected in surface waters of China , whereas levels of 4‐NP were 1 order of magnitude higher (Supplemental Data, Table S4) . On a global scale, the BPA concentration in river water of Tianjin is considered relatively low.…”
Section: Discussionmentioning
confidence: 81%
“…Nitro-PAHs and heterocyclic PAHs are suggested as additional target compounds, with a probable further relevance of PAEs and nonylphenol (cf. this study; Cui et al, 2009;Floehr et al, 2013, in press;Jin et al, 2014). Furthermore, endocrine activity should be tested for its significance as a relevant mode-of-action in the area, as it could be determined in several sections of the Yangtze River (as reviewed by Floehr et al, 2013).…”
Section: Resultsmentioning
confidence: 86%
“…EDCs are considered to alter hormone levels leading to reproductive effects in aquatic organisms at environmental concentration continuously (Tisler et al, 2016). Previous toxicological studies have demonstrated reproduction was identified as the most sensitive endpoint for EDCs (Caldwell et al, 2008;Jin et al, 2014). Reproductive toxicity includes fecundity, rate of fertilization, hatchability, gonadosomatic index sustained for multiple generations, and the synthesis of vitellogenin (VTG) in fish (Martino-Andrade and Chahoud, 2010).…”
Section: Introductionmentioning
confidence: 99%